Dealing with Iguanas in the South Florida Landscape - William H. Kern, Jr. (EDIS, 2004)
Due to Florida's prominence in the exotic pet trade, iguanas imported as pets have escaped or been released, and are now established in South Florida. This has created unique problems for Florida's homeowners and businesses. South and Central Florida's subtropical climate allows these large herbivorous (plant-eating) lizards to survive, reproduce, and become part of the Florida environment. This document is Fact Sheet ENY-714, a series of the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: August 2004.